Corpo e cuidado de si: a dança como experiência formativa - Folchini, Heloisa Andreola (2020)
The research presented aims to investigate the body and dance, with a greater focus on the latter. Some central questions were elaborated conducting the study: What is dance education? Is there a dance as a self-care and a body care concurrently? Is it possible for the subject to transform himself into this practice to be a better subject, both with himself and in his other relationships? Its main objective is to answer the question that arises from the research problem: What does it mean to understand dance as self-care? The study is a bibliographic research, readings and reflections, with a hermeneutic focus and interpretation and dialogue of the classic text. The dissertation is structured in three chapters. Initially, a diagnosis of the contemporary body is made, presenting external factors - such as fashion, the media, consumerism, ideologies and, the sociability criteria based on the body -, which affect it and condition it in some way. . To this end, theorists such as Francisco Ortega and Jurandir Freire Costa are used. In the second chapter, Michel Foucault and his study of self-care is taken, linking it to body care through aspects of dietetics, aesthetics and ethics. This step allows us to reach the main point of the dissertation, its third and final chapter, which addresses dance and its formative role. Dance is themed as a process of self-formation and self-discipline of the practitioner, developing sensitive skills in the one who dances, having it as a practice of freedom, which allows to understand it as self-care. In this sense, it is understood as a way of life, from an ethical basis, and as an exercise in which the subject is transformed, through this practice, towards the best of himself. It is concluded that dance can be configured as self-care with subjective and ethical implications, allowing the subject to become involved in an aesthetic of existence, becoming empathic and sensitive to himself, the other and the world.